Water structure near the surface of Weyl semimetals as catalysts in photocatalytic proton reduction - Gujt, Jure; Zimmer, Peter; Zysk, Frederik; Suess, Vicky; Felser, Claudia; Bauer, Matthias; Kühne, Thomas D. (STRUCTURAL DYNAMICS, 2020)
In this work, second-generation Car-Parrinello-based mixed quantum-classical mechanics molecular dynamics simulations of small nanoparticles of NbP, NbAs, TaAs, and 1T-TaS2 in water are presented. The first three materials are topological Weyl semimetals, which were recently discovered to be active catalysts in photocatalytic water splitting. The aim of this research was to correlate potential differences in the water structure in the vicinity of the nanoparticle surface with the photocatalytic activity of these materials in light induced proton reduction. The results presented herein allow explaining the catalytic activity of these Weyl semimetals: the most active material, NbP, exhibits a particularly low water coordination near the surface of the nanoparticle, whereas for 1T-TaS2, with the lowest catalytic activity, the water structure at the surface is most ordered. In addition, the photocatalytic activity of several organic and metalorganic photosensitizers in the hydrogen evolution reaction was experimentally investigated with NbP as the proton reduction catalyst. Unexpectedly, the charge of the photosensitizer plays a decisive role for the photocatalytic performance.
CRIS-Team Scopus Importer:2022-04-14